Model pembelajaran auditory intellectually repetition terhadap peningkatan kemampuan berpikir kritis matematis siswa - Madi Amin; Muliana Muliana; Rohantizani Rohantizani (Journal of Didactic Mathematics, 2021)
The purpose of this study was to determine the mathematical critical thinking ability of students who were taught using the Auditory Intellectually Repetition learning model was better than the mathematical critical thinking skills of students who were taught through a scientific learning approach. This study uses a quantitative approach and the type of research used is quasi-experimental research. The population in this study were 11th grade students of SMA Negeri 5 Simeulue Barat, the samples in this study were two classes selected using a nonprobability sampling technique of purposive sampling type, namely class 11 IPA-1 as an experimental class using the Auditory Intellectually Repetition model and class 11 IPA-2 as a control class using a scientific approach. The data processing technique uses SPSS version 25 with the results of the study showing that: the value of Sig (p-value) > 0.05), it is accepted that it is 0.629 in the experimental class and 0.273 in the control class so that the data has a normal distribution. The t-test analysis of students' mathematical critical thinking skills was obtained 0.001 < 0.05, then Ho was rejected and Ha was accepted. This means that the mathematical critical thinking ability of students who are taught with the Auditory Intellectually Repetition learning model is better than the mathematical critical thinking skills of students who are taught with a scientific learning approach.